Bentuk Pertanggungjawaban Hukum Pihak yang Wanprestasi dalam Perjanjian Berdasarkan Kitab Undang-Undang Hukum Perdata - Effendy, Yulius; Anggawira, Anggawira (FOCUS, 2025)
The negligence, in the form of a breach of contract by one party in a marble mining investment collaboration agreement in South Sulawesi, result in legal liabilities imposed on the negligent party. These liabilities include compensating for losses, paying interest, and continuing the contract as stipulated in the Indonesian civil code. Regarding the legal consequences arising from the breach of contract, the negligent party risks being subjected to civil lawsuits through litigation (in court) or non-litigation (outside court) processes. The lawsuits may demand negligent party to compensate for the losses suffered by the other party, pay any interest incurred due to breach, and fulfill the remaining terms of the investment collaboration agreement.